Editorial - Guzman, Carolina; Dison, Laura (Critical Studies in Teaching and Learning, 2023)
We are pleased to present the June 2023 issue of Critical Studies in Teaching and Learning (CriSTaL). In this issue, we bring together six thought-provoking papers that explore critical perspectives and different aspects of teaching and learning in higher education. The first two papers in this issue deal with issues of inequality. The first alludes to the pandemic and the ways in which it has affected students' experiences, while the second looks at the inequalities faced by rural students in higher education as a result of the neglect and undervaluation of their experiences, skills and knowledge within the university environment. The next two papers focus on challenges to teaching and learning in the classroom, the first on learning-centred assessment practices and the second on teachers' reflections on the quality and modes of thinking in writing intensive courses.